2020
DOI: 10.1001/jamacardio.2020.2488
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Associated With Out-of-Hospital Cardiac Arrests and Resuscitations During the Novel Coronavirus Disease 2019 Pandemic in New York City

Abstract: hospital cardiac arrests peaked at 305 cases, nearly a 10-fold increase from the prior year. OBJECTIVE To describe the characteristics (race/ethnicity, comorbidities, and emergency medical services [EMS] response) associated with outpatient cardiac arrests and death during the COVID-19 pandemic in NYC. DESIGN, SETTING, AND PARTICIPANTS This population-based, cross-sectional study compared patients with out-of-hospital cardiac arrest receiving resuscitation by the NYC 911 EMS system from March 1 to April 25, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
308
2
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(370 citation statements)
references
References 39 publications
25
308
2
20
Order By: Relevance
“…Casefatality rates have been between 4.5 and 15-fold higher 16 . Seattle/ King County (USA) and Padua (Italy) similarly reported no increase in OHCA incidence during the COVID-19 pandemic 5,6 but in Victoria, we demonstrated no increase in OHCA incidence, low COVID-19 incidence, and low COVID-19 case-fatality. Findings out of Padua also reported delays in key response time intervals (call-to-dispatch and dispatch-to-departure) 7 , however, the major delays we identified occurred after arrival at scene.…”
Section: Discussioncontrasting
confidence: 61%
“…Casefatality rates have been between 4.5 and 15-fold higher 16 . Seattle/ King County (USA) and Padua (Italy) similarly reported no increase in OHCA incidence during the COVID-19 pandemic 5,6 but in Victoria, we demonstrated no increase in OHCA incidence, low COVID-19 incidence, and low COVID-19 case-fatality. Findings out of Padua also reported delays in key response time intervals (call-to-dispatch and dispatch-to-departure) 7 , however, the major delays we identified occurred after arrival at scene.…”
Section: Discussioncontrasting
confidence: 61%
“…In terms of predictors, preliminary evidence from 191 SARS-CoV2 infected patients in Wuhan showed that the most common factors associated with poor prognosis include advanced age, the presence of pre-existing conditions such as hypertension and diabetes mellitus (DM), as well as elevated inflammatory markers, amongst others [5]. These findings have been mostly consistent in other countries [6][7][8]. In KSA, the earliest national data (March, 2020) involving 1519 confirmed cases (mean age 36 years) also showed that the most common comorbidities were hypertension (8.8%) and DM (7.6%) [9].…”
Section: Introductionmentioning
confidence: 95%
“…5 King Saud University Medical City, Riyadh 12746, Saudi Arabia. 6 Obesity, Endocrine, and Metabolism Center, King Fahad Medical City, Riyadh 11564, Saudi Arabia. 7 Chair for Biomarkers of Chronic Diseases, Biochemistry Department, College of Science, King Saud University, Riyadh 11451, Saudi Arabia.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…At the same time, hospitalizations for acute cardiovascular conditions, including myocardial infarction, heart failure, and stroke, have declined precipitously ( 5 , 6 , 7 ). These patterns have raised concern that patients may be avoiding hospitals because of fear of contracting severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) and that some may have died of cardiovascular conditions without seeking medical care ( 8 , 9 ). Other factors, including the deferral of outpatient cardiovascular visits, diagnostic testing, and semi-elective procedures, as well as greater strain on health care systems, may also have unintended effects on higher-risk patients.…”
mentioning
confidence: 99%